2019
DOI: 10.2147/pgpm.s230201
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pharmacogenomics And Hypertension: Current Insights</p>

Abstract: Hypertension is a multifactorial disease that affects approximately one billion subjects worldwide and is a major risk factor associated with cardiovascular events, including coronary heart disease and cerebrovascular accidents. Therefore, adequate blood pressure control is important to prevent these events, reducing premature mortality and disability. However, only one third of patients have the effective control of blood pressure, despite several classes of antihypertensive drugs available. These disappointi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 150 publications
(192 reference statements)
1
56
0
1
Order By: Relevance
“…Each subclass of calcium channel blocking agent binds at a specific location. For example, dihydropyridines (e.g., amlodipine and nifedipine) exert vascular selectivity, verapamil has cardiac selectivity, and diltiazem can act in both the heart and blood vessels [ 1 , 18 ]. Figure 1 presents the mechanism of CCB’s action.…”
Section: Calcium Channel Blocking Agentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Each subclass of calcium channel blocking agent binds at a specific location. For example, dihydropyridines (e.g., amlodipine and nifedipine) exert vascular selectivity, verapamil has cardiac selectivity, and diltiazem can act in both the heart and blood vessels [ 1 , 18 ]. Figure 1 presents the mechanism of CCB’s action.…”
Section: Calcium Channel Blocking Agentsmentioning
confidence: 99%
“…Numerous studies have indicated that the single-nucleotide polymorphisms (SNPs) in genes encoding different ion channels, including the large-conductance voltage and calcium-sensitive potassium channel β1 ( KCNMB1 ), the voltage-gated calcium channels α1C ( CACNA1C ), α1D ( CACNA1D ) and β2 ( CACNB2 ), and ERG potassium channel ( KCNH2 ), can modify the antihypertensive responses to CCB and the risk of adverse cardiovascular outcomes [ 1 , 19 , 20 , 21 , 22 , 23 ]. Furthermore, variations in the genes coding the family of HECT domain E3 ubiquitin ligases (NEDD4L) and ATP-binding cassette subfamily B member 1 (ABCB1) have been shown to participate in the regulation of blood pressure (BP) in response to anti-hypertensive drugs [ 11 , 16 ].…”
Section: Calcium Channel Blocking Agentsmentioning
confidence: 99%
See 3 more Smart Citations